Isolasi dan Uji Aktivitas Amilase pada Bakteri yang Berasal dari Hulu sungai Logawa Banyumas - Adinda Salwa Amellia Putri Al Saqaj; Oviliana Laurentia Saputri; Farah Ispramudita Septiyanti; Yuriza Eshananda (Fakultas Perikanan dan Ilmu Kelautan, 2025)
Amylase is an enzyme that is widely used in various industrial fields. Amylase-producing microorganisms, especially bacteria, are a potential source that continues to be explored to this day. This study aims to isolate and test amylase from the natural environment, such as the water of the Logawa River. The methods used in this study include sampling, bacterial isolation, purification, amylolytic activity testing, micromorphological and macromorphological characterization, and catalase testing on bacterial isolates. The results of the study obtained three selected bacterial isolates based on macromorphological characteristics. Amylolytic activity testing with 1% substrate showed that two isolates, namely HL 1-2 and HL1-3, had amylolytic indices of 0.97 and 1.38, respectively, which were indicated by the formation of a clear zone around the colony after 48 hours of incubation at 28 °C. All isolates are Gram-positive bacteria with positive catalase test results. The results of the study indicate that the Logawa River, especially in the upstream part, has the potential to be a source of amylolytic bacteria that can be bioprospected further.